2001
DOI: 10.1007/s007740170010
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical examination of osteoblastic activity in op/op mice with or without injection of recombinant M-CSF

Abstract: Osteopetrotic (op/op) mice do not exhibit bone remodeling because of defective osteoclast formation caused by the depletion of macrophage colony-stimulating factor (M-CSF). In the present study, we investigated tibial bones of op/op mice with or without prior injections of M-CSF to determine whether osteoclast formation and subsequent bone resorption could activate osteoblasts, which is known as a "coupling" phenomenon. In op/op mice, no osteoclasts were present, but the metaphyseal osteoblasts adjacent to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Without osteoclasts, osteoblastic population, osteoblastic bone formation and bone mineralization are markedly diminished in op/op mice, which lack the macrophage colony-stimulating factor [12,13]. One of our studies demonstrated that cell coupling between osteoclasts and preosteoblasts must take place for the parathyroid hormone-driven bone anabolic effect to occur [14].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Without osteoclasts, osteoblastic population, osteoblastic bone formation and bone mineralization are markedly diminished in op/op mice, which lack the macrophage colony-stimulating factor [12,13]. One of our studies demonstrated that cell coupling between osteoclasts and preosteoblasts must take place for the parathyroid hormone-driven bone anabolic effect to occur [14].…”
Section: Introductionmentioning
confidence: 65%
“…In vivo animal studies have shown that bisphosphonate administration negatively affects mineral apposition rate, which suggests reduced osteoblast activity [15][16][17][18]. This may be due to hindrances in the "coupling phenomenon", the partnership with osteoclasts that seems to be necessary for osteoblastic activity during bone remodeling [12][13][14]. High-dose bisphosphonate administration disrupts the coupling between osteoclastic bone resorption and osteoblastic bone formation [34], and several in vivo studies have shown the effects of such disruption of cell coupling on osteoblasts [17,35].…”
Section: Discussionmentioning
confidence: 99%
“…Mice with absent osteoclasts, known as op/op mice, have induced failure of bone remodeling and exhibit osteopetrosis by reduced bone resorption. (18) Although no report has discussed the relationship between M-CSF and kidney stone formation, granulocyte-macrophage colony-stimulating factor (GM-CSF) could be involved in hypercalciuria and bone mineral loss in calcium kidney stone formation via peripheral blood monocyte activation. (19) Cxcl1 encodes chemokine (C-X-C motif) ligand 1 (CXCL1), known as growth-related oncogene 1 (GRO1), which could enhance the adhesion of monocytes to matrix protein, (20) and is involved in the atherogenic recruitment of monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise function of macrophages in kidney stone formation and elimination could not be determined, and the possibility that we observed renal responses to crystal formation remains. To confirm the role of macrophages in kidney stone formation, an in vivo study using op/op mice (18) or an in vitro study using cultured renal tubular cells and macrophages to detect the paracrine systems between cells is necessary. Moreover, the mechanism of removing intratubular crystals to the interstitial area should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that cell coupling with osteoclasts in vivo is necessary for preosteoblastic differentiation into mature osteoblasts to deposit new bone in response to parathyroid hormone (21). Consistently, op/op mice, an- other mouse model lacking osteoclasts (9,18,19,22) revealed the extremely-reduced osteoblastic activity in long bones (26), and defective bone mineralization (30). Taken together, the presence of osteoclasts is important for cell coupling to activate osteoblastic cells in bone remodeling sites in vivo.…”
Section: Immnolocalization Of Ephrinb2 and Ephb4 In C-fosmentioning
confidence: 51%